Comparison of Capillary Versus Venous Blood for the Diagnosis of Plasmodium falciparum Malaria Using Rapid Diagnostic Tests. (27th January 2021) - Gorret, Abalinda M; Muhindo, Rabbison; Baguma, Emma; Ntaro, Moses; Mulogo, Edgar M; Deutsch-Feldman, Molly; Juliano, Jonathan J; Nyehangane, Dan; Boyce, Ross M
Abstract: We enrolled 250 febrile children in western Uganda to compare the results of malaria rapid diagnostic tests (RDTs) when using capillary vs venous blood. Participants were tested with 4 different RDT types. Polymerase chain reaction testing was performed as the reference standard. Sensitivity and specificity were broadly similar across RDT types and sampling method. Agreement between sample type was high, ranging from 0.95 to 0.99. When following the manufacturer's recommended interpretation, only 5 tests would have resulted in a different clinical diagnosis. These results demonstrate that malaria RDTs perform similarly when using capillary or venous blood in febrile children with Plasmodium falciparum malaria. Abstract : Malaria rapid diagnostic test (RDT) results obtained from capillary or venous blood are frequently interpreted as interchangeable, despite a lack of comparative studies. Our results demonstrate that RDTs perform similarly by source of blood in febrile children with Plasmodium falciparum malaria.